PENGARUH STRATEGI DIVERSIFIKASI, INTELLECTUAL CAPITAL DISCLOSURE, PERENCANAAN PAJAK TERHADAP NILAI PERUSAHAAN - Faiz Dzikrullah; Arian Firmansyah; Dirvi Surya Abbas (Fakultas Ekonomi Universitas IBA, 2025)
One moderating component in this study is government-owned businesses. The relationship between intellectual capital (VAICTM: added value of human capital, added value of capital used, and added value of structural capital), diversification strategy (Hierschman Herfindah Index), and firm value (Tobin's Q) is examined in this study. Companies listed between 2013 and 2017 on the Indonesia Stock Exchange (BEI) are the subject of this study. 59 businesses were chosen as samples for this study using the purposive sampling technique. Multiple linear regression and traditional assumption tests were used to analyze the regression data. Research indicates that intellectual resources have a greater impact on firm value than diversification and tax planning techniques. Tax preparation and diversification tactics may have an impact on a company's worth.